Predicting rapid response to cognitive-behavioural treatment for panic disorder: The role of hippocampus, insula, and dorsolateral prefrontal cortex. - Reinecke, A; Thilo, K; Filippini, N; Croft, A; Harmer, C (2014)
Although cognitive-behavioural therapy (CBT) is an effective first-line intervention for anxiety disorders, treatments remain long and cost-intensive, difficult to access, and a subgroup of patients fails to show any benefits at all. This study aimed to identify functional and structural brain markers that predict a rapid response to CBT. Such knowledge will be important to establish the mechanisms underlying successful treatment and to develop more effective, shorter interventions. Fourteen unmedicated patients with panic disorder underwent 3 T functional and structural magnetic resonance imaging (MRI) before receiving four sessions of exposure-based CBT. Symptom severity was measured before and after treatment. During functional MRI, patients performed an emotion regulation task, either viewing negative images naturally, or intentionally down-regulating negative affect by using previously taught strategies of cognitive reappraisal. Structural MRI images were analysed including left and right segmentation and volume estimation. Improved response to brief CBT was predicted by increased pre-treatment activation in bilateral insula and left dorsolateral prefrontal cortex (dlPFC) during threat processing, as well as increased right hippocampal gray matter volume. Previous work links these regions to improved threat processing and fear memory activation, suggesting that the activation of such mechanisms is crucial for exposure-based CBT to be effective.